WASPADA BAHAN BERBAHAYA PADA MAKANAN JAJANAN ANAK SEKOLAH BEWARE OF DANGEROUS INGREDIENTS IN SCHOOL SNACKS - Nazwa Muthia Rahmasari; Amalia Rahmadani2 Isnaini Putri; Isnaini Putri (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The food we consume today, especially in elementary schools, is often processed. These foods are full of chemicals and additives, such as preservatives, flavor enhancers, colorings, and sweeteners. They also lack the nutrients children need daily. If we don't change this, it will likely be detrimental to students' health in the near future. It can also slow their growth and development over time. The research was conducted in grade VI C of Elementary School Teacher Training and Education (PGSD) at STKIP Al Maksum Langkat. The results obtained from this study indicate that nuggets contain formaldehyde and borax after being tested with turmeric and dragon fruit. Instant noodles contain formaldehyde after being tested with turmeric and dragon fruit. Sausages contain formaldehyde and borax after being tested with turmeric and dragon fruit. Meatballs contain formaldehyde and borax after being tested with turmeric and dragon fruit. Ale-ale contains formaldehyde and borax after being tested with turmeric and dragon fruit.